PEMBUATAN KEJU NABATI RENDAH LEMAK BERBAHAN DASAR KACANG TUNGGAK DENGAN BAKTERI Lactobacillus bulgaricus DAN Streptococcus thermophilus - barokah, yola (Jurnal Gizi, 2018)
Utilization of cowpeas as raw material of vegan cheese be alternative food for people who can’t consume the common cheese. This research was conducted to know about calcium content, fat content, lactic acid content and organoleptic. The method of this research is experimental using 3 treatments: Utilization concentration of bacteria Lactobacillus bulgaricus dan Streptococcus thermophilus with 1%, 2%, and 3% concentrations. This research showed utilization concentrations of bacteria Lactobacillus bulgaricus dan Streptococcus thermophilus 2% indicated calcium content 129.58 mg/100gr and fat content 1.16%. 3% concentration indicated 14929.66 mg/L lactic acid. The result of organoleptic test is cowpeas cheese is the most favorite omong the panelist with 2% concentration of lactic acid bacteria. This research also showed that using Lactobacillus bulgaricus dan Streptococcus thermophilus to produced cowpeas cheese affect the organoleptic test for taste, color, smell dan texture parameter.